Contributions to the Jubilee Symposium of the Photonics Society of Poland for its 15th anniversary by Optica - Roll, Claus; Woggon, Ulrike (Photonics Letters of Poland, 2023)
In this article we summarize our presentations as two representatives from Optica (formerly OSA) at the ceremony celebrating the 15th anniversary of the Photonics Society of Poland. The first presentation provides an update of the dynamic industrial revolution occurring in light science and technologies. In the second presentation, recent activities of Optica in Europe are shown.